Parafibromin as a Diagnostic Instrument for Parathyroid Carcinoma-Lone Ranger or Part of the Posse? - C. Christofer Juhlin; Anders Höög (International Journal of Endocrinology)
The diagnosis of parathyroid carcinoma requires an invasive growth pattern or metastases detected at histopathological examination; unfortunately, not all carcinomas exhibit visible malignant properties at the initial assessment. Therefore, immunohistochemical markers have been sought for the recognition of parathyroid malignancy. In 2003, the Hyperparathyroidism 2 (HRPT2) gene was found mutated in the majority of sporadic parathyroid carcinomas investigated, and studies regarding the protein product parafibromin proposed loss of nuclear parafibromin as a highly sensitive marker for the detection of parathyroid carcinoma. Recent studies have not fully reproduced these findings, as subsets of carcinomas display positive parafibromin immunoreactivity, and fractions of adenomas demonstrate absent expression. Overall, parafibromin is a marker of value to the endocrine pathologist, but it cannot be recommended as a sole indicator of parathyroid carcinoma. Additional markers such as protein gene product 9.5 (PGP9.5) and adenomatous polyposis coli (APC) could complement parafibromin when assessing malignant potential of parathyroid tumours.